Dampak Stres Terhadap Kesuburan dan Siklus Menstruasi Wanita - Ainun Ganisia; Tasya Rara Ajeng Pramista (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Introduction: stress is a condition of a person due to stimulation or pressure. Women are susceptible to emotional disorders or stress. Many factors affect irregular menstrual patterns, including stress. Irregular menstrual cycles can have serious impacts on women's health which will affect the metabolic, fertility, sexual, and reproductive systems. The inability to reproduce naturally can cause shame, guilt, and low self-esteem. These negative feelings can cause various levels of depression, anxiety, stress, and poor quality of life. This article aims to determine the effect of stress on women's menstrual cycles and fertility. Research method: a literature review with narratives from various research results related to stress and the menstrual cycle, as well as women's fertility. Data sources: from national and international journals indexed from 2017 to 2023. Results: increased production of CRH and cortisol causes decreased ovulation. This decreased ovulation will affect the length of the proliferation and secretion period, thereby affecting the menstrual cycle. Stress affects menstrual cycle disorders and women's fertility. Conclusion: stress influences changes in women's menstrual cycles and fertility so women need counseling and support during therapy.